EFFECT OF ORIENTATIONS PRE-OPERATIVE BY MULTIPROSSIONAL GROUP ON ANXIETY OF PATIENTS UNDERGOING CARDIAC SURGERY - Almeida, Silvania Martins (2013)
Aim: to compare the level of anxiety in patients undergoing cardiac surgery before and after the multi-professional team intervention. Method: this is a cohort study which patients undergoing coronary artery bypass grafting and valve replacement surgeries. The State-Trait Anxiety Inventory (STAI) was used for data collection. This instrument was administered before and after the multi-professional team intervention with subsequent comparison of means. Results: the sample with 20 patients was composed mostly (60%) by male subjects with mean age 58 ±15.7 years. Before intervention, the trait anxiety mean was 46.5 ±9.43, and 43.5 ±12.8 for state anxiety; after intervention, state anxiety mean was 40.15 ±10.06 (p = 0.020). Conclusion: the anxiety level in patients has significantly decreased when before and after moments are compared.